2007
DOI: 10.1016/j.etap.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen effects on the early life stages and reproduction of Japanese medaka (Oryzias latipes)

Abstract: Tamoxifen is widely used in the treatment of breast cancer and can enter the aquatic environment in municipal wastewater. To evaluate potential effects on embryonic development of Japanese medaka, fertilized eggs were exposed to tamoxifen at 1-625 g/l for 14 days. Adverse effects on hatchability and time to hatching only occurred at 125 and 625 g/l. Reproductive effects were assessed by exposing adults for 21 days to the same dose range. At all concentrations tested, tamoxifen significantly increased plasma vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 34 publications
1
36
1
Order By: Relevance
“…To our knowledge, only one paper has reported the significant alteration of genotypic sex ratio in fish exposed to tamoxifen. Sun et al (2007) found a significant increase in the proportion of F1 male O. latipes relative to the controls when breeding pairs medaka were exposed to anti-estrogen tamoxifen for 21 days. They think that the observed change in sex ratio may be caused by differential sensitivity of spermatozoa (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…To our knowledge, only one paper has reported the significant alteration of genotypic sex ratio in fish exposed to tamoxifen. Sun et al (2007) found a significant increase in the proportion of F1 male O. latipes relative to the controls when breeding pairs medaka were exposed to anti-estrogen tamoxifen for 21 days. They think that the observed change in sex ratio may be caused by differential sensitivity of spermatozoa (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…At a concentration of 5000 ng/L, E3 led to sex reversal of four males, which indicated that high concentrations of E3 can induce feminization of fish. Sex reversal in fish exposed to EDCs has been reported previously and may involve estrogenic chemicals eliciting female characteristics in males or androgenic chemicals producing male traits in females (Iwamatsu et al, 2000;Sun et al, 2007). Sex reversal of male fish is considered a consequence of the transformation from testes to ovaries during early gonadal development under the direct influence of environmental estrogens (Zha et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, coexposure to TAM could not neutralize the impaired reproductive capacity caused by E2, and complete reproductive failure occurred at the highest concentration (250 g/L). In our previous study (Sun et al, 2007a), exposure to TAM alone affected the reproductive capacity detrimentally at a concentration of only 625 g/L, but no paired medaka ceased spawning. Therefore, these findings demonstrate that combined exposure to E2 and TAM can impair the reproductive function more severely than exposure to each component alone.…”
Section: Discussionmentioning
confidence: 99%